Efektivitas Pengelolaan Ruang Terbuka Hijau dalam Perspektif Implementasi Kebijakan Lingkungan di Kota Cimahi - Achdiat Achdiat (PERSPEKTIF, 2026)
Rapid urbanization and economic development have intensified pressure on urban environmental quality, including the provision and management of green open spaces (GOS) in Cimahi City, Indonesia. Although previous studies have widely examined the ecological and social benefits of urban green spaces, limited attention has been paid to evaluating their management effectiveness from the perspectives of public organizational effectiveness and environmental governance. This study aims to analyze the effectiveness of green open space management in Cimahi City by employing the theoretical perspectives of organizational effectiveness and environmental policy implementation. A qualitative phenomenological approach was adopted. Data were collected through observations, purposive interviews with officials of the Environmental Agency and community members, and document analysis. The data were analyzed using the interactive model of Miles, Huberman, and Saldaña. Management effectiveness was assessed based on indicators including the achievement of green open space targets, institutional capacity, adequacy of resources (land, budget, and facilities), program implementation, community participation, and environmental outcomes. The findings reveal that green open space management has not yet been effective, as the proportion of public green open space remains below the statutory target, institutional implementation capacity is inadequate, land and budget constraints persist, and collaborative public participation remains limited. This study contributes to the literature on environmental governance and public administration by demonstrating that the effectiveness of green open space management should be evaluated not only through administrative compliance but also through the organization's implementation capacity to produce sustainable ecological and social outcomes.